Direito ao meio ambiente e o aquecimento global : sobrevivendo ao acordo de Paris (COP-21) - Fredes, Andrei Ferreira (2016)
Men and society were always intimately connected to nature, and ambiental factors were always key to the social and political organization of society and, at least on an inderect manner, to law. Nevertheless the conscience of the intimate and unbreakable bond between men, society, law and nature only started taking shape on the western culture of law around 1960 and 1970, initially from the new philosophical conceptions that no longer stated nature as something in full disposition to men and, since then, Environmental Law has significantly developed and became a constitutional right and reached the status of fundamental right in many of the modern constitutions, besides many international treaties that mention the right to a healthy environment as a real human right, and many specific infraconstitutional legislation about various aspects of environmental protection. Sadly the development of the huge amount of rules aiming to guarantee a healthy environment still falls short of facing its biggest threat, that is global warming. In spite of recent achievements about this subject in international level, like the Paris Agreement signed on december 2015, and national legislations like the National Climate Change Policy in Brazil, we are still in a time of pratical shortcomings on this subject, where a logic of sustentability that claims that it tries to equilibrate possibly incompatible dimensions ends up turning development itself into unsustainable development, specially for the more poor ones that, without doubt, will be the most affected by the nefarious results of the advancements of global warming, which we are already experiencing and, as the science points out, soon will intensify even more should law stay motionless.